Metaphor Translation in Sandra Brown’s Novel “Exclusive” - Herlina Libra Lisa (The Explora, 2020)
The objectives of this study were to 1) find the meaning of metaphors found, 2) analyze the strategies used in translating them into Indonesian version and 3) identify the types of shifts found in the translation of Sandra Brown Novel “Exclusive” with its Indonesian version entitled “Berita Ekslusif”. There are two types of metaphor namely dead metaphor and live metaphor. This study was restricted in analyzing live metaphors based on theory of Larson(1998) that was applied to analyze the meaning of metaphor by identifying the topic, image, point of similarity, and/or non figurative meaning, as well as her other theory of strategies used for translating metaphors. The types of shift were identified and analyzed by following theory of Catford (1974). Data were collected through library research by note taking the live metaphors found in the data source. Many examples of metaphorical expressions were collected from the novel. Then, the collected data were analyzed by the theory concerned. The result of the study showed that it is hard to identify the live metaphor if the topic and/or the point ofsimilarity left implicit. There are four strategies applied by the translator in translating live metaphors in this study, they were translating by keeping the metaphorical image, translating as simile, substituting to the metaphor in the target language which had the same meaning and translating without keeping the metaphorical imagery. The most strategy used in translating live metaphors in this study is the last one without keeping the metaphorical imagery. All types of category shifts occurred in this translation, such as class shift, structure shift, unit shift, and intra system shift.